Toward Seamless Mobility-as-a-Service - Alexandra Hoess; Jonathan Lautenschlager; Johannes Sedlmeir; Gilbert Fridgen; Vincent Schlatt; Nils Urbach (Business & Information Systems Engineering, 2024)
With growing awareness of sustainability and convenience expectations, customers are increasingly demanding integrated and seamless mobility in the form of mobility-as-a-service (MaaS). However, as centralized MaaS platforms have thus far failed to integrate a critical share of mobility service providers (MSPs), travelers lack opportunities to efficiently combine the various mobility services required for seamless end-to-end itinerary coverage. Particularly, MSPs often refuse to collaborate by devolving control over customer interfaces or sensitive data owing to threats of market power concentration. While alternative blockchain-based approaches aim to provide equal market access, they cannot sufficiently align competing business goals and face substantial problems resulting from the replicated processing of sensitive data. Both researchers and practitioners have recently suggested decentralized digital identity management enabled by digital wallets as a promising mechanism to exchange verifiable identity attributes while mitigating problems related to data aggregation. Following a design science research approach, the article accordingly explores how digital wallets can address the shortcomings of existing approaches to MaaS. It contributes a novel IS~architecture and principles for a design at the nexus of centralized and decentralized solutions to mitigate tensions between cooperation and competition. Further, the findings indicate that when building decentralized solutions, one should also consider components beyond blockchain and smart contracts.
Keywords: 000; Coopetition; Digital identity; Digital wallet; MaaS; Self-sovereign identity